(untitled) (Research, Society and Development, 2021)
The year 2020 indelibly marked the history of humanity, leaving deep marks on the ways of being and being in society. Almost everyone was touched by the “new normal” imposed by the Covid-19 Pandemic, which radically changed the forms of social relations that imply any physical proximity, impairing the possibilities of being together, of socializing in groups, of collective action. The school routine was abruptly interrupted. Face-to-face teaching was suspended without any idea of ​​how and when it would return, and the damage caused to education was substantial. This rupture was reestablished, at a distance, thanks to Education and Communication Technologies, perceived as fundamental to face the moment, bringing teachers and students closer together. This writing is bibliographical in nature, reflective in nature, which is based on Gramsci’s theoretical basis and aims to make some reflections on being a teacher and the function of the school, more specifically on the strategies for using educational technologies in the context of pandemic, in the light of the Gramscina theory. We can infer that this study contributes in its findings to reflections on educational practices, raising important questions about educational policy, teacher development and training, the limits and possibilities of strategies for using Educational Technologies and being a teacher as a responsible figure. by the constant search for quality education.